Analisis Hasil Friction Stir Welding Aluminium 5083-H112 Menggunakan Taper Threaded Cylinder Pin dengan Variasi Kecepatan Rotasi dan Translasi: Result Analysis of Friction Stir Welding of Aluminum 5083-H112 Using Taper Threaded Cylinder Pin with Variation in Rotational and Translational Speed - Slameto Wiryolukito; Johanes Pratama Wijaya Wijaya (Jurnal Metalurgi dan Material Indonesia, 2020)
The technique of joining aluminum with the conventional fusion welding method is still difficult to be applied, because aluminum series has low weldability, therefore, a new method is developed, friction stir welding (FSW) which is a solid-state welding. In this study, the optimization process of the translation speed was carried out using aluminum 5083-H112 workpiece with a thickness of 10 mm. This optimization process includes observing and testing the effect of translational speed on microstructure, strength, hardness and toughness on the weld area. The tool that is used in this optimization process is a taper threaded cylinder pin type, with pin diameters 4 and 7 mm, pin height 9.5 mm, left hand threaded, and the material used is AISI H13. The optimization process produces 3 translation speed parameters, 31.5 mm/min; 50 mm/min; and 63 mm/min with constant rotational speed, 1250 rpm. These three parameters change the microstructure in the weld area, where there are 3 microstructure areas observed, weld nuggets (WN), thermomechanically affected zone (TMAZ), and heat affected zone (HAZ). Whereas mechanical properties such as strength, hardness and toughness tend to decrease along with the increase in welding translational speed.